2021
DOI: 10.1002/oby.23313
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated efficacy of pediatric obesity treatment during the COVID‐19 pandemic

Abstract: The COVID-19 lockdown has had pervasive effects on children, including school closures, a shift to remote learning, and suspension of youth sports and recreational activities. Children gain weight at an accelerated rate when not in school (1), which has been attributed to greater engagement in obesogenic behaviors when children's days are unstructured (2). There is emerging evidence that children's physical activity, sedentary time, eating patterns, and sleep routines deteriorated during the COVID-19 lockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Accelerated weight gain could not be prevented in children who participated <1 year in our lifestyle intervention. These results are in agreement with outcomes of Appelhans et al [23] who reported an increase in the BMI z-score in children with overweight and obesity measured 6 and 12 months after participation in a lifestyle intervention during the COVID-19 pandemic. Although weight gain might be reduced or other positive effects of the guiding of children and families might be present, shortterm lifestyle intervention seems to be insufficient to halt accelerated weight gain during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Accelerated weight gain could not be prevented in children who participated <1 year in our lifestyle intervention. These results are in agreement with outcomes of Appelhans et al [23] who reported an increase in the BMI z-score in children with overweight and obesity measured 6 and 12 months after participation in a lifestyle intervention during the COVID-19 pandemic. Although weight gain might be reduced or other positive effects of the guiding of children and families might be present, shortterm lifestyle intervention seems to be insufficient to halt accelerated weight gain during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Lifestyle intervention is the treatment of choice in children with overweight and obesity, resulting in significant weight loss and improvement of cardiovascular parameters [ 20 , 21 ]. However, the recent literature indicates that treatment efficacy of pediatric obesity programs provided during the pandemic is markedly reduced [ 23 ]. The effect of participating in lifestyle intervention prior to the pandemic on weight gain during the pandemic, and possible protective effects, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Among these subjects, approximately 60% reported an increase in body weight, which was significantly greater in adolescents than in children (13). Consistently, Appelhans et al demonstrated a significant weight gain among low-income, racial minority, obese children followed during the Covid-19 period compared to those followed in the pre-pandemic period at 12-month assessment (14).…”
Section: Discussionmentioning
confidence: 74%
“…Consistently, Appelhans et al. demonstrated a significant weight gain among low-income, racial minority, obese children followed during the Covid-19 period compared to those followed in the pre-pandemic period at 12-month assessment ( 14 ).…”
Section: Discussionmentioning
confidence: 87%
“…Although the transition of pediatric weight management interventions (PWMIs) to telehealth following the onset of the pandemic has been shown to be feasible, (11) delivery of these programs has been overall affected. Suspension of school-based interventions and decreased e cacy of PWMIs have been reported; (12,13) other disciplines have had similar experiences given the need for diverting resources to pandemic response. (14) Evidence-based PWMIs are necessary to mitigate the impact of obesity on child health, particularly in communities that are at highest risk.…”
Section: Introductionmentioning
confidence: 99%